SEMANTIC RELATIONS IN TOPICAL SEQUENCES OF ENGLISH BUSINESS DISCOURSE - Vira Yushkevych (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article presents the analysis of the content organisation of English business discourse, which can be hierarchical and linear. The overview of scientific papers demonstrates that only hierarchical organisation of discourse has been thoroughly studied, while the linear one is still the subject of investigation. The focus of this paper is the analysis of the linear-hierarchical organisation of the realised themes and topics in it and existing semantic relations between them. The linear-hierarchical organisation of the content in English business discourse is considered as a set of models: a monotopical one, which displays the realisation of the same theme and/or topic within the exchange, and a polytopical one, i.e. a content model that presents the unfolding of various themes and/or topics within the same exchange. The types of a polytopical model are identified as follows: first type demonstrates topical sequence, in which various topics belonging to one theme are combined; second type shows topical sequence, in which various topics belonging to different themes are combined. The types of semantic relations between the elements of the model are examined. The author has identified that in the monotopical model relations of generalisation, specification, modification, support and closing are realised, and in polytopical model - relations of digression and change. Topic change in its turn can be sharp/incohesive or gradual/coherent.